Researching Women at Auckland University of Technology - Julich, SJ; Mansfield, J; Terrell, J; Garet, C; Jovanovic, L (Philosophy of Education Society of Australasia, 2006)
This Report was first published as Researching Women at Auckland University of Technology by AUT Women on Campus, 2004 (ISBN: 1-877314-25-0). Research was conducted under the auspices of the Women on Campus Research Group. Authors: Shirley Jülich and Janet Mansfield; Editor: Jane Terrell; Research Assistants: Catherine Garet and Ljiljana Jovanovic. Original publication was sponsored by AUT Printsprint. In republishing Researching Women at Auckland University of Technology, ACCESS has been faithful to the original text making changes to format as required to fit ACCESS style. In this report, the Women on Campus research group aim to contextualise our own existence and image the performances of what we have named Researching Women within the coercive and self-regulatory system of tertiary education at Auckland University of Technology (AUT). The collection and analysis of data concerning research outputs by women through quantitative analysis in the first instance, has marked the terrain for asking further questions through different approaches. We examine researching women in both the global and the local context, highlighting in a preliminary way some of the barriers to the fullest participation of academic women. Knowledge about researching women is constructed as a site of contestation in a literature review that involves some critical processing and goes beyond an annotated account of the literature.